2008
DOI: 10.1093/annonc/mdm450
|View full text |Cite
|
Sign up to set email alerts
|

[18F]2-fluoro-2-deoxy-D-glucose positron emission tomography (FDG PET) as a diagnostic tool for neurofibromatosis 1 (NF1) associated malignant peripheral nerve sheath tumours (MPNSTs): a long-term clinical study

Abstract: FDG PET and PET CT is a sensitive and specific diagnostic tool for NF1-associated MPNST. Other PET tracers will be required to solve the problem of predicting tumour grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
143
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(160 citation statements)
references
References 17 publications
9
143
1
1
Order By: Relevance
“…Noninvasive modalities that can reliably differentiate NF from MPNST would significantly contribute to the management of NF1 patients. Recently, FDG-PET has been shown by us and other investigators to be a promising noninvasive modality with the potential to differentiate malignant from benign tumors (30,31). Fig.…”
Section: Differentiating Nf From Mpnst Using Noninvasive Pet/ct Imagingmentioning
confidence: 99%
“…Noninvasive modalities that can reliably differentiate NF from MPNST would significantly contribute to the management of NF1 patients. Recently, FDG-PET has been shown by us and other investigators to be a promising noninvasive modality with the potential to differentiate malignant from benign tumors (30,31). Fig.…”
Section: Differentiating Nf From Mpnst Using Noninvasive Pet/ct Imagingmentioning
confidence: 99%
“…Although the cutoff values of SUVmax vary among such reports, many papers reported SUVmax values of 3-4 (10,(16)(17)(18)(19). In our study, malignant neurogenic tumors showed high FDG uptake and benign tumors showed low FDG uptake, and the SUVmax had 90.0% sensitivity, 91.7% specificity, and 98.3% accuracy with a cutoff value of 4.8.…”
Section: Discussionmentioning
confidence: 45%
“…Positron emission tomography (PET-CT) -PET-CT is of great value in monitoring lesions with the potential for malignant transformation in NF1, especially in the evaluation of the symptomatic plexiform neurofibromas 58 . Due to the frequency and severity of MPNST associated to NF1, PET-CT scan could be useful in the following situations: a) when the plexiform tumor growth is inconsistent with the child's growth track; b) in the presence of neurological deficit; c) changes in tumor texture; and finally d) when patient reports an inexplicable and progressive pain.…”
Section: Nf1 Imaging Studiesmentioning
confidence: 99%